COVID ANIMATIONS: Bringing film to life (Presentation) - Lugemwa, Abbas; Gibb, Tom (My University, 2023)
Traditional journalists, politicians, elders, and opinion leaders dominated ‘information’ and communications about the pandemic. Scientists were either side-lined, or didn’t know how to communicate the right information they had, had no resources to do it or all the information there was, wasn’t reaching them in time. The ‘COVID ANIMATIONS: Bringing film to life’ project employed a collaborative approach to science engagement and journalism with the aim of bridging the gap between COVID-19 scientific evidence generated and public health messaging. Using science-based community engagement to fight COVID-19 through animations and film journalism. Themes: -Creating COVID-19 community awareness and response through film -Mitigating the negative impact of COVID-19 on; Maternal and child health and HIV/AIDS care services